2016
DOI: 10.18632/oncotarget.10236
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid functional parameters and correlative autoantibodies as prognostic factors for differentiated thyroid cancers

Abstract: To evaluate the effect of preoperative thyroid functional parameters and thyroid autoantibodies on aggressive clinicopathologic features and lymph node metastasis (LNM) of differentiated thyroid cancer patients. Four hundred twenty consecutive patients with initial surgery were enrolled from July 2010 to July 2015. The associations between aggressive clinicopathologic and LNM factors and thyroid functional & autoantibodies parameters were analyzed. Higher levels of TSH, TGAb or TMAb were found in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…In the current study, univariate analysis results suggested that Tg and Anti-Tg were related to ipsi-LLNM ( P range, .000–.001). The further multivariate logistic analysis showed that Tg > 100.01 ng/mL and Anti-Tg > 89.43 IU/mL were both independent risk factors for ipsi-LLNM in agreement with Li’s reports [ 21 ]. Based on these results, we conclude that Tg and Anti-Tg might be correlated with tumor aggressiveness and prognosis in patients with PTC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, univariate analysis results suggested that Tg and Anti-Tg were related to ipsi-LLNM ( P range, .000–.001). The further multivariate logistic analysis showed that Tg > 100.01 ng/mL and Anti-Tg > 89.43 IU/mL were both independent risk factors for ipsi-LLNM in agreement with Li’s reports [ 21 ]. Based on these results, we conclude that Tg and Anti-Tg might be correlated with tumor aggressiveness and prognosis in patients with PTC.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies [ 21 , 22 ] have shown that thyroid stimulating hormone (TSH) is closely related to the occurrence and development of PTC. However, it is not clear whether there is an association between other thyroid function indicators and LLNM.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, univariate analysis results suggested that Tg and Anti-Tg were related to ipsi-LLNM (P range, .000 -.001). Further multivariate analysis showed that Tg > 100.01ng/ml and Anti-Tg > 89.43 IU/ml were also independent risk factors for ipsi-LLNM, which was in agreement with Li's reports (19). Based on these results, we may conclude that Tg and Anti-Tg may be correlated with tumor aggressiveness and prognosis in patients with PTC, and the measurement could give additional information for predicting aggressiveness and ipsi-LLNM.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies (19,20) have shown that thyroid stimulating hormone (TSH) is closely related to the occurrence and development of PTC, but the relationship between other thyroid functional indicators and LLNM is inconclusive, for example, preoperative serum thyroglobulin (Tg), anti-thyroid stimulating hormone (Anti-Tg) and anti-thyroid peroxidase (Anti-TPO).…”
Section: Introductionmentioning
confidence: 99%
“…TSH is a well-established risk factor of thyroid cancer. The association between TSH and CLNM was only observed by few of studies [ 3 , 27 ]. The current study showed that although significant differences were observed in HT, TSH, TGAB, and TMAB between male and female groups, the predictive value of HT, TSH, TGAB, and TMAB for CLNM was not differed by gender.…”
Section: Discussionmentioning
confidence: 99%